2018
DOI: 10.61426/sjbcm.v5i3.816
|View full text |Cite
|
Sign up to set email alerts
|

Lean Project Management and Performance of Building Construction Firms in Nairobi City County, Kenya

BENJAMIN MOCHUMARI ONYANCHA,
GLADYS KIMUTAI

Abstract: This researcher sought to find out the inefficiencies that could be the cause of underperformance in order to fill the gap through applications of more efficient and cost effective methods. The researcher therefore sought to analyse the experiences of construction companies in terms of the problems of wastes, high costs, bottlenecks, inventory control and how performance has been impacted. The research was done in Nairobi City County because many of the construction operation were conducted in Nairobi. The fin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 9 publications
1
0
0
Order By: Relevance
“…The statement that certification of engineers in the construction industry provides confidence of quality implementation of projects had a mean score of 3.57 and a standard deviation of 1.450. These results concurred with Nyaga and Otieno (2018) study that found out that Projects are constrained by inadequate planning skills that are required for effective planning for project success; Project planning is complicated and risky, hence requires varying skills sets for successful project implementation and management; Increasing complexity in the projects with pressure of time and costs has led to the introduction of high quality software and hardware which requires skilled planning.…”
Section: Project Team Competencysupporting
confidence: 84%
“…The statement that certification of engineers in the construction industry provides confidence of quality implementation of projects had a mean score of 3.57 and a standard deviation of 1.450. These results concurred with Nyaga and Otieno (2018) study that found out that Projects are constrained by inadequate planning skills that are required for effective planning for project success; Project planning is complicated and risky, hence requires varying skills sets for successful project implementation and management; Increasing complexity in the projects with pressure of time and costs has led to the introduction of high quality software and hardware which requires skilled planning.…”
Section: Project Team Competencysupporting
confidence: 84%